Studi Analisis Komparasi Pendidikan Karakter dalam Kurikulum Sekolah Dasar di Indonesia, Singapura, dan Jepang - Irmayati Irmayati; Hermansah Hermansah; Lukman Nulhakim; Atin Fatimah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Character education in elementary schools plays a crucial role in establishing the foundation of character development within formal education. Currently, character education in elementary schools has not been maximized, leading to behavioral deviations among students. Improving character education requires serious efforts, one of which is through a comparative analysis study of character education in the elementary school curriculum of Indonesia, Singapore, and Japan. This study aims to (1) analyze the implementation and impact of character education in the elementary school curriculum of Indonesia, Singapore, and Japan, and (2) examine the similarities and differences in the implementation of character education in these three countries. This research is a literature review study using a qualitative method with a comparative analysis approach to character education implementation in elementary schools in Indonesia, Singapore, and Japan. In this literature review, we analyzed 60 articles from Scopus and Google Scholar published between 2015 and 2024, along with other relevant documents. The analysis results indicate that the implementation of character education in elementary schools varies across countries, with each having its own distinctive characteristics and approaches aligned with national characteristics. The similarities in character education implementation in Indonesia, Singapore, and Japan include its integration into the curriculum, being taught through subjects, and being implemented through habituation activities or school culture. Meanwhile, the differences lie in the implementation strategies, which are adapted to the characteristics and needs of students in each country.